REGIONAL DIGITAL STRUCTURAL-PETROLOGICAL MODELING OF CRISTALLINE MASSIVE OF TERRITORY OF UKRAINE - Khrushchov, D.P.; Belevtsev, R.Ya.; Bobrov, А.B.; Geychenko, M.V.; Artemenko, G.V.; Lobasov, А.P (Institute of Geological Sciences, NAS of Ukraine, 2016)
The target of the communication is the presentation of a concept for regional digital structural-petrological modeling of crystalline massive within the limits of a state territory. Methodological principles, methods, preliminary results available and examples of models are reflected. Digital structural-petrological model is a computer reflection of geological object including it’s structural and qualitative characteristics. The results achieved: obtaining of integrated complex digital structural-petrological of crystalline massive on formational basis by regional principle upon state scall level. The pbjectives of modeling is to found multiscale multipurpose basement for information supervision of all issues and kinds of geological activity connected with variable use and protection of geological environment.